Αγγλικά - Διδακτικοί Μύθοι 1 - Δ'-ΣΤ' Δημοτικού Επ. 86 (Υπουργείο Παιδείας και Θρησκευμάτων, 2020)
: [♪ Μουσική Τ Amen Hello kids! And how are you? Findt? Are you ready for another story? I'm here to tell you another story. But before I start with my story, I want to ask you some questions. Do you know why it is good to listen to and read to stories? Oh, it's fun! Yes, you're right, it is fun. It is fun and it is helpful. Can you give me another reason why it is good to listen to stories and read stories? Oh, the words, you learn more words. Of course, of course. Because stories are made of a lot of words. And some words you know and you remember them. And if you don't know other words, you understand them from the whole meaning of the story. Now I want to give me another reason why listening to stories or reading stories is good for you. What was that? Oh, you learned facts. Of course, you learned facts. Remember the other time when we did the alligator and the crocodile? And what did we say about the teeth? That an alligator has 64 teeth? And that your mom or your dad or me have only got 32 teeth? That is a fact. Good, you gave me three reasons. And can you give me a fourth reason why it is good to read stories? What? You are proud. You're proud. Really, why? Why are you proud? Because you understand a story in a foreign language. Yes, yes, I understand that. I'm going to give you a fifth reason. Another reason why it's good to listen to stories is because we understand how we think, how we feel and how we act. And we understand how other people think, feel and act. And we understand each other better. And we also understand how people from other countries, from far away countries understand. So stories bring us together. Now, before I start with my story, I would like you to take a piece of paper or a notebook and a pencil. Why? Well, because I would like you to write the names of the characters of the story. And I will tell you why this is good at the end. Okay? Have you got your pen? And have you got everything? I'm waiting. I'm waiting a bit. So, are you ready to listen to my story? Yes, yes, yes? Okay, come with me. I'll take you to the forest again. I like going to the forest. Once upon a time, in a forest, there were some animals. There was a pig, there was a flamingo, there was a crocodile, there was a snake and many other animals. And they were talking. Now, their story is going to start with the tortoise. Now, a tortoise is this lovely animal. You see, what do we know about a tortoise? That it moves slowly, yes. And that it's got its, what is that? The house? The cover? Yes, but how do we call that? We call it shell. You can write this down. The house of the tortoise, the cover is its shell. And it's very hard. It's not as soft as our skin. And now the word shell means other things as well. For example, if you go to the sea, on the sand, you might find this shell. Or you might find this shell. There was a sea creature, a sea animal here once. Now, these are the covers, alright? So, a shell is really the cover. Now, the tortoise is walking very slowly in the forest. And it sees something round. And it sees something shiny, shiny. And it sees something metal, golden. And there are some little diamonds on that. There are some little diamonds. Can you tell me what it is? What do you think it is? A ring? Oh yes, a ring is shiny. It is round. It's good diamonds but it is not a ring. I will help you. A king or a queen or a prince or a princess wears this thing. Yes, it is a crown. It is a crown. Now, the tortoise sees the crown and it likes it. And puts the crown on its head. And moves very slowly to the rest of the animals. And the tortoise says to the animals, Look everybody, it fits me perfectly. It fits me like a glove. It was made for me. I'm a real king. And now the animals start laughing and laughing and laughing. You, the king, impossible. And the tortoise says, why is that? And the goat comes forward and says, you are too slow, too slow. And a king must have a white beard like me. And with that, the goat snatches, snatches, snatches the crown and puts it on its head. And then it says to all the animals, and you repeat after me, Look everybody, it fits me perfectly. It fits me like a glove. It was made for me. I'm a real king. And now the animals start laughing and laughing and laughing. And the goat says, why is that? And Flamingo comes forward and says, Don't be silly. That is not a white beard. That is a hairy chin. Your chin is hairy. And anyway, a king must have style. And I'm the only one here that has style. And with that, the flamingo snatches the crown, puts it on the head and says, and follow me. Look everybody, it fits me perfectly. It fits me like a glove. It was made for me. I'm a real king. Now again, the animals start laughing and laughing and laughing. And they say, you, the king, impossible. And the flamingo says, why is that? And then the snake comes forward and says, Slow, a king must be clever and must be smart and do clever things. And with that, the snake catches, snatches the crown, puts it on the head and weighs, goes up, up, up and stands with its booty up and that crown on its head and says, look everybody, it fits me perfectly. It fits like a glove. It was made for me. I am a real king. And again, the animals start laughing and laughing and laughing. And they say, you, the king, impossible. Why is that, says the snake. And the pig comes forward and says, because a real king must be wonderfully round like me. And with that, the pig snatches the crown, puts it on its head and says, please with me, follow me. Look everybody, it fits me like a glove. It was made for me. I am a real king. And of course, the animals start doing what? Laughing, of course, and laughing and laughing and say, you, the king, impossible. And the pig says, why is that? And it's then that the crocodile comes forward with a big smile and all the teeth showing. And the crocodile says, don't make me laugh. A real king must be tough. A real king must be feared, just like me. And with that, the crocodile snatches the crown and puts it on its head and says, look everybody, it fits me perfectly. It fits me like a glove. It was made for me. I am the real king. Now the animals, they are afraid. They don't say anything. But then the elephant comes forward and says, wait a minute, not so quickly. A real king must be old and wise. A real king must have good memory. And with that, the elephant takes the crown with its tusk and puts it on its head. And it says, look everybody, it fits me perfectly. It fits me like a glove. It was made for me. I am the real king. You, the king, again the animals did not want to say anything because they were not sure. But then comes the ape, a big monkey. And the monkey comes running, you know, climbing down from the big tree and snatches the crown, puts it on its head and says, a real king must be clever and must have strong hands and strong legs and must be as athletic as me. And with that, the monkey starts running, running, running, singing, I'm the king, I'm the king, I'm the king of the jungle. And now all the animals start following king. Of course, the tortoise is really very behind, it cannot follow. And the goat says, that is mine. And the flamingo says, wait, that is mine. And the snake says, I'll catch you. And the pig says, I cannot run anymore. And the crocodile says, I'll get you some time. And the elephant stays behind and just looks and walks, not very quickly. And you know what's happening, the monkey is holding branches and there's a lot of noise with all the animals following behind. And with all that noise and all that's happening, then suddenly there is a crush. Just crush. And a lion appears. And the monkey is so frightened, the monkey cannot do anything. So the lion takes the crown, puts it on its head and says, look, everybody, it fits me perfectly. It was made for me. I am the real king of the jungle. And the animals are looking and first the flamingo starts clapping and then all the animals. And then they start saying, yes, yes, yes, we agree. You are the king, you are the king of the jungle. And so the lion is the king of the jungle. And that is the end of the story, but it's not the end of the lesson. You see, let's try and see what this story is telling us. When the animals, when the goat and flamingo and the snake, when they see the tortoise with the crown, they are all jealous. And they all want to have the crown. And they all think that they are the kings. Why is that? I don't know. Can you think about it? Why is that happening? Now, another thing I need to ask you is this. What must a real king be like? I mean, must a king be a little silly like the goat? Must a king be one with style like the flamingo? Or does a king have to be smart and make tricks like the snake? Or must he be a little round and beautiful looking or tough and the others should be afraid of him? Or must a real king be wise, old with good memory? Or be very athletic and play tricks as well? Now, in class I would really like to have all your opinion. And I'm sure you're going to have different opinions. Now, remember I told you to have a little paper and to write the characters of the story. Now that you have all the characters of the story, you can remember the story. And what can you do with that? Well, go and tell the story to your friends, to your mum and dad, to anybody that you know. And you know what? Stories must travel. Stories go from mouth to ear and then back to mouth and from country to country and all over the world. And remember, if you wrote those words, what we learned today, if we didn't know, was shell, the shell of the tortoise. We saw shiny, we saw the word diamond, we saw the word crown, the word snatch and tough. And that was remembering some of the words. And that is the end of the story, the end of the lesson and see you again soon. Bye bye!